A região metropolitana da Baixada Santista: uma análise a partir dos fatores que favorecem a capacidade de governança e governabilidade regional - Lippi, Mariana Ferreti (2011)
Since the XIX century, when the first national park was established, the management of the protected areas have been evolving and improving thus becoming an important mechanism for the conservation of biodiversity and one of the major efforts of state government intervention. With that in mind this dissertation presents an in-depth analysis of the institutional arrangements of environmental politics that influence the common use of the natural resources of the local population of the “Serra do Mar” State Park. The items being analyzed for this argumentation are: the theoretical conflict between environmentalism and social-environmentalism; the problematic use of the common pool resources associated to the need, or not, of governmental intervention; the programs and actions of the São Paulo State Government for the consolidation of the conservation units under full protection; and the variables that compose the institutional arrangements of the environmental politics in the cases examined, “Cota 400” e “Água Fria”, located in Cubatão. In face of the institutional arrangements of the environmental politics for the management of the protected areas this dissertation pursues understanding which is the best situation for the conservation of the natural resources, with cases studied by the model proposed by Elinor Ostrom. The case analysis demonstrated a fragile institutional performance of the community for the sustainable use of common pool resources.